Regional Poverty and Its Determinants in Iran - Shooshtarian, Ashan; Bakhshoodeh, Mohammad (Journal of Income Distribution®, 2009)
Household data were used in this study to measure regional poverty and its determinants separately for ten defined zones in rural and urban areas in Iran in 2005. The non-parametric approach was used to estimate poverty lines for each zone and the effect of poverty determinants on poor and non-poor households was studied applying probit models. The findings indicate that poverty rate, gap, and intensity are higher in the urban areas. Family size, level of literacy, and asset ownership are amongst the various determinants of poverty. In general, the success of antipoverty programs depends highly on recognition of regional differences.